An educational-evaluation study for street children in Rumah Impian Foundation - Aulia Ninda Haryoni; Istiana Hermawati (Graduate School, Universitas Negeri Yogyakarta, 2019)
This research aims to evaluate the education of street children at Rumah Impian Foundation in Yogyakarta. This is an evaluation research using a responsive evaluation model with a naturalistic qualitative approach. The evaluation stages carried out in this study consist of Rational, Anteccendent, Transaction, and Outcome. The sampling technique used was purposive sampling with snowball sampling because the data were obtained from the community of the subjective sample, or in other words, the sample used is very rare and is grouped in a set. The data were analyzed using qualitative analysis techniques by Milles and Huberman. The results of the study show that, at the rational stage, the background of the educational concern for street children starts with a sense of caring about the street children’s future that is worth fighting for. In the antecedent stage, there is a conformity input between the volunteer, apprenticeship membership, and the street children’s education needs, in the form of policies and recruiting volunteers to be a companion to street children. At the transaction stage, the process between the foundation and street children education is appropriate, meaning that the foundation has facilitated the education needed by street children both formally and non-formally, in the form of increasing their skills through courses. Thus, there is a match between what was done in the previous stages and its results, showing that there are street children who reach their dreams, as a result of the foundation's efforts to continue knitting their dreams through intensive activities and assistance.